STUDI FOTODEGRADASI CONGO RED MENGGUNAKAN UV/ZnO/REAGEN FENTON - Widiantini, Ni Luh Putu; Sibarani, James; Manurung, Manuntun (Jurnal Kimia (Journal of Chemistry); Vol. 7, No. 1 Januari 2013, 2013)
The study of photodegradation of Congo Red using UV light, with addition ZnO catalyst, H 2 O 2 and Fe 2+ has been carried out. This study included the determination of optimum amount of ZnO, H 2 O 2 , Fe 2+ , pH optimum and the determination of system which shows the most effective in Congo Red photodegradation. The results showed that the optimum conditions to degradate 100 ppm of Congo Red solution were 60 mg of ZnO, 4 ml of H 2 O 2 (0,0392 mol), 20 mg FeSO 4 (0,0013 mol)  and pH 5. The highest percentage of degradation was 93,6093 + 0,12 % reached using UV/ZnO/H 2 O 2 / Fe 2+ system at 5 hour photodegradation time. In this processes addition of ZnO, H 2 O 2 , and FeSO 4 , and pH were important parameters to increase the percentage of photodegradation.
Keywords: Photodegradation, Congo Red, ZnO catalyst, Fenton Reagen